Vocabulary Skills in Reading English of Grade 5 Pupils in New Normal within The Schools Division of Zambales: Basis for Innovative Strategies on Vocabulary Development - Cruz, Liezel Laulita (Future Science / FSH-PH Publications, 2025)
This action research, conducted during the 1st Quarter of School Year 2023-2024 in the Schools Division of Zambales, aims to evaluate the vocabulary skills of Grade 5 pupils in English reading and propose innovative strategies for vocabulary development. Employing the descriptive-developmental method, the study encompasses the entire Grade 5 population (1,892 respondents) in central schools, utilizing total enumeration. Moreover, research investigates the current status of vocabulary skills through a vocabulary test and assesses the adequacy of existing materials. It also identifies pupils' needs, explores innovative strategies, and evaluates their acceptability. Statistical tools such as frequency distribution, rank, means, and standard deviations are employed for quantitative analysis. The qualitative description utilizes a rating scale from DepEd Order No. 8 s. 2015. Meanwhile, the findings reveal a mixed landscape of proficiency among Grade 5 students, with commendable competence in synonyms, antonyms, and general word association. Existing instructional materials are well-received, indicating high adequacy. Teachers emphasize the importance of diverse strategies and materials, aligning with contemporary educational approaches. The proposed innovative workbook receives overwhelmingly positive evaluations from English teachers, affirming its potential effectiveness. In conclusion, the study highlights the need for targeted interventions to address specific vocabulary challenges, continued use of existing materials with enhancements, and the implementation of a comprehensive curriculum. The positive reception of the innovative workbook suggests its potential as an effective tool for vocabulary improvement in Grade 5 pupils. Future research should delve into the causes of learners' challenges in vocabulary skills for a deeper understanding.